1995
DOI: 10.1111/j.1749-6632.1995.tb44651.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Osteopontin in a Macrophage Cell Line and in Transgenic Mice with Pulmonary Fibrosis Resulting from the Lung Expression of a Tumor Necrosis Factor‐α Transgene

Abstract: The expression level of osteopontin (OPN) mRNA was found to be increased in a macrophage cell line in the presence of recombinant tumor necrosis factor-alpha (TNF-alpha). OPN mRNA level was also explored in the lungs of transgenic mice which were expressing TNF-alpha in type II pneumocytes, a condition leading to pulmonary alveolitis and progressive fibrosis. OPN mRNA was significantly increased in the lungs of these transgenic mice. In situ hybridization showed that it was localized mostly in alveolar macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
1
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 18 publications
2
31
1
2
Order By: Relevance
“…As shown in Fig. 6B, OPN was significantly induced by TNF-α stimulation, as published elsewhere (Miyazaki et al, 1995). However, contrary to our expectation, regardless of the concentration, butein did not inhibit TNF-α-induced OPN expression.…”
Section: Effect Of Butein On Opn-induced Pro-mmp-7 Expression In Ht-2contrasting
confidence: 83%
“…As shown in Fig. 6B, OPN was significantly induced by TNF-α stimulation, as published elsewhere (Miyazaki et al, 1995). However, contrary to our expectation, regardless of the concentration, butein did not inhibit TNF-α-induced OPN expression.…”
Section: Effect Of Butein On Opn-induced Pro-mmp-7 Expression In Ht-2contrasting
confidence: 83%
“…It was, therefore, suggested that macrophages are the main source of OPN, which is taken up secondarily by tumor cells [2]. In macrophages, the inflammatory cytokines interleukin-1 b and tumor necrosis factor-a appear to upregulate OPN expression [13]. Furthermore, OPN expression is elicited in response to pathological stimuli by various cell types, including endothelial cells, smooth-muscle cells [14], and T-lymphocytes [17], resulting in chemotaxis.…”
Section: Discussionmentioning
confidence: 99%
“…It is, however, also possible that the increased transcription rate seen in demyelinating disease may be a secondary event marking the established inflammatory process. For example, it is known that pro-inflammatory cytokines such as tumour necrosis factor and interleukin-1β or nitric oxide, which are elevated in multiple sclerosis, can induce osteopontin gene expression [9,14,16].…”
Section: Discussionmentioning
confidence: 99%